Analisis Efektivitas Pengelolaan Anggaran Belanja Operasional Kantor Pencarian Dan Pertolongan Kelas B Nias - Evirniat Gulo; Aferiaman Telaumbanua; Sukaaro Waruwu; Maria Magdalena Batee; Sophia Molinda Kakisina (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
The aim of this research is to determine the level of effectiveness of operational budget management for the Class B Nias Search and Rescue Office. On this occasion the researcher conducted research by using data and dealing directly with information parties deemed necessary and related to the problem under study, namely as much as 5 people who are officials from the Nias Class B Search and Rescue Office. Based on research results, the effectiveness level in 2020 was 79.707%, and in 2021 it was 87.694%, still less effective. In this research, the factors that cause an ineffective level of shopping effectiveness are due to a lack of human resources both in terms of quantity and quality, and the Covid-19 pandemic.